2019
DOI: 10.1097/md.0000000000016693
|View full text |Cite
|
Sign up to set email alerts
|

Current status and job satisfaction of village doctors in western China

Abstract: To strengthen rural health services, the Chinese government has launched a series of policies to promote health workforce development. This study aims to understand the current status of village doctors and to explore the factors associated with village doctors’ job satisfaction in western China. It also attempts to provide references for further building capacities of village doctors and promoting the development of rural health service policy. A multistage stratified sampling method was used to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In our study, we found that 99.04% of invited doctors met the requirements, which is much higher than the percentage of legacy face-to-face consultations. Only 27.5% of doctors in primary medical institutions (eg, township hospitals and village clinics) have proper professional titles, which is one of the reasons that they could not provide high-quality medical services [ 37 , 38 ]. As one motivation for the rapid development of telemedicine, patients of primary hospitals could also receive better diagnoses and treatments from experienced experts with senior titles.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that 99.04% of invited doctors met the requirements, which is much higher than the percentage of legacy face-to-face consultations. Only 27.5% of doctors in primary medical institutions (eg, township hospitals and village clinics) have proper professional titles, which is one of the reasons that they could not provide high-quality medical services [ 37 , 38 ]. As one motivation for the rapid development of telemedicine, patients of primary hospitals could also receive better diagnoses and treatments from experienced experts with senior titles.…”
Section: Discussionmentioning
confidence: 99%
“…[40]- [41] In addition, the increase in workload extended the part-time working hours of VCDs. Previous studies have shown that most VCDs work part-time in agricultural production, commercial activities or temporary employment, [20] in addition to providing health services, to effectively provide for their families. However, with the increasing workload, VCDs have had to spend more time working to provide health services, resulting in the continuous reduction in income from their other part-time jobs.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding VCDs' JS, Zhang Qi et al studied the current level of the JS of VCDs in western China, and the results showed that 44.6% of VCDs expressed dissatisfaction with their work. [20] Zhang Xiaoyan et al described the current situation of VCDs' JS in Jiangxi Province, and the results showed that 87.28% of VCDs expressed dissatisfaction. [21] Ding Haiyun et al described the current JS of VCDs in Nanjing, and the results showed that 46.5% of VCDs were dissatis ed with their job.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increase in workload extended the part-time working hours of VCDs. Previous studies have shown that most VCDs work part-time in agricultural production, commercial activities or temporary employment [24], in addition to providing health services, to effectively provide for their families. However, with the increasing workload, VCDs have had to spend more time working to provide health services, resulting in the continuous reduction in income from their other part-time jobs.…”
Section: Satisfaction With Job Rewards Internal Work Environment and Organizational Management Showed A Downward Trend After The First Rimentioning
confidence: 99%
“…It was an important topic in this research area. Zhang et al [24] studied the current level of the JS of VCDs in western China, and the results showed that 44.6% of VCDs expressed dissatisfaction with their work. Zhang et al [25] described the current situation of VCDs' JS in Jiangxi Province, and the results showed that 87.28% of VCDs expressed dissatisfaction.…”
Section: Introductionmentioning
confidence: 99%